Evaluation of textile wastewater treatment in sequential anaerobic moving bed bioreactor - aerobic membrane bioreactor. (June 2021) - Kozak, Melike; Cırık, Kevser; Dolaz, Mustafa; Başak, Serden
Graphical abstract: Highlights: Sequencing AnMBBR-AeMBR was successful by means of raw textile wastewater treatment. Membrane biofouling can be directly correlated to Alphaproteobacteria . Silicon originated from textile wastewater caused chemical membrane fouling. PAC was effective for improving contaminant removal and fouling. Abstract: In this study, the treatability of real textile wastewater [dissolved organic carbon (DOC): 500 mg/L), color: 6383 Pt-Co, sulfate: 362 mg/L)] was investigated in sequential anaerobic moving bed bioreactor (AnMBBR) and aerobic membrane bioreactor (AeMBR). AnMBBR was filled with 40 % career material (Kaldnes K1). The effect of different hydraulic retention times (HRTs) (6−48 h) and powdered activated carbon (PAC) addition (1 g/L) was investigated for system optimization. Sequential AnMBBR- AeMBR was successfully operated for textile wastewater treatment corresponding to 92 %, and 90 % dissolved organic carbon (DOC) and color removals, respectively. The effluent quality, dropped under 45 Pt-Co and 18 mg/L effluent values, was relatively high and complianted with discharge standards. The Fourier transform infrared spectroscopy (FT-IR) analysis showed that primary amines are successfully removed in AeMBR effluent. Fouling in AeMBR was increased when HRT was reduced, however, improved by 90 % at PAC addition conditions. Except for soluble microbial products (SMP) and soluble extracellular polymeric substances (EPS), it was observed that silicon (Si) (13.16 %) has an important role in fouling which was confirmed by scanning electron microscopy (SEM) and Energy-Dispersive X-ray (EDX) analysis. Additionally, microbial community structures indicated that the membrane fouling can be caused by Alphaproteobacteria (80 %) which was the dominant culture in the biofilm layer at a maximum fouling rate.